Advanced Practice Registered Nurses: Gateway to Screening for Bipolar Disorder in Primary Care - Kriebel-Gasparro, Ann Marie (Open Nurs J, 2016)
OBJECTIVE: The goal of this mixed methods descriptive study was to explore Advanced Practice Registered Nurses’ (APRNs’) knowledge of bipolar disorder (BPD) and their perceptions of facilitators and barriers to screening patients with known depression for BPD. METHODS: A mixed method study design using surveys on BPD knowledge and screening practices as well as focus group data collection method for facilitators and barriers to screening. RESULTS: 89 APRNs completed the survey and 12 APRNs participated in the focus groups. APRNs in any practice setting had low knowledge scores of BPD. No significant differences in screening for BPD for primary and non primary care APRNs. Qualitative findings revealed screening relates to tool availability; time, unsure of when to screen, fear of sigma, symptoms knowledge of BPD, accessible referral system, personal experiences with BPD, and therapeutic relationships with patients. CONCLUSION: Misdiagnosis of BPD as unipolar depression is common in primary care settings, leading to a long lag time to optimal diagnosis and treatment. The wait time to diagnosis and treatment could be reduced if APRNs in primary care settings screen patients with a diagnosis of depression by using validated screening tools. These results can inform APRN practice and further research on the effectiveness of screening for reducing the morbidity and mortality of BPDs in primary care settings; underscores the need for integration of mental health care into primary care as well as the need for more APRN education on the diagnosis and management of bipolar disorders.